2022
DOI: 10.1371/journal.pone.0264789
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and associated risk factors in patients hospitalized due to COVID-19 in a Peruvian reference hospital

Abstract: Objectives To determine the risk factors for in-hospital mortality in patients with COVID-19 from a Peruvian national hospital. Methods Retrospective cohort study of medical records of patients with COVID-19 hospitalized at Hospital Nacional Hipólito Unanue (HNHU) during the months of April to August 2020. The dependent variable was in-hospital mortality. Independent variables included sociodemographic and clinical characteristics, physical examination findings, oxygen saturation (SaO2) at admission, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
3
9
1
Order By: Relevance
“…It was found that the risk factor of being elderly (40–59, 60–79 or 80+ years old) increases the possibility of death compared to hospitalized adults under 40 years of age. This finding is in line with those reported in other studies conducted for different countries [ 14 , 38 , 39 , 40 ], and it can be interpreted due to the influence of immunosenescence (immune aging), which negatively contributes to a low immune response to vaccination of the elderly. Notice that this immunological fact is not unique to anti-COVID-19 vaccines, occurring with influenza, pneumonia, tetanus, and hepatitis B vaccines as well [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was found that the risk factor of being elderly (40–59, 60–79 or 80+ years old) increases the possibility of death compared to hospitalized adults under 40 years of age. This finding is in line with those reported in other studies conducted for different countries [ 14 , 38 , 39 , 40 ], and it can be interpreted due to the influence of immunosenescence (immune aging), which negatively contributes to a low immune response to vaccination of the elderly. Notice that this immunological fact is not unique to anti-COVID-19 vaccines, occurring with influenza, pneumonia, tetanus, and hepatitis B vaccines as well [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…The risk of death for hospitalized patients with or without diabetes or chronic lung disease was comparable. These findings differ from those reported elsewhere, where it is suggested that these conditions have an impact on mortality [ 15 , 55 , 56 , 57 ]. However, the lack of association observed here could be explained by the “diabetes/obesity paradox” and by the physiological readjustment during the critical stage of the disease [ 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Numerous investigations have evaluated factors associated with COVID-19 death in hospitalized patients; most of them have been conducted over a short period, and only a few of them have been conducted in Peru [ 10 , 11 , 12 , 13 , 14 , 15 ]. Of the studies carried out in Peru, one included information from three healthcare centers [ 12 ] and another described factors associated with ICU admission among hospitalized patients in a high-altitude setting [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a lower Sa/FiO 2 ratio and a decreased lymphocyte count were associated with death by COVID-19 ( Henry et al., 2020 ; Huang and Pranata, 2020 ; Booth et al., 2021 ; Pons et al., 2021 ; Gopalan et al., 2022 ; Soto et al., 2022 ). It should be noted that lymphopenia might occur due to consequent apoptosis of activated CD4+T cells by SARS-CoV-2 ( Shen et al., 2022 ), thereby inducing immune suppression.…”
Section: Discussionmentioning
confidence: 99%